Great lives from history - Magill, Frank Northen, 1907-1997. (Pasadena, Calif. : Salem Press, 1987)
A five-volume set of biographical sketches, arranged alphabetically, of more than 476 prominent individuals from all walks of life who have made significant contributions and impact on British and Commonwealth history and development. Includes bibliographies for each individual entry.
V.1: A-Cav -- v. 2: Cax-Gag -- v. 3: Gai-Law -- v. 4: Lea-Rey -- v. 5: Rho-Z.
Includes bibliographical references and indexes.
Keywords: Biography -- 20th century; Commonwealth countries -- Biography; Great Britain -- Biography